2018
DOI: 10.1016/j.corsci.2018.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Hot corrosion of borate melt and interface chemistry of borate-coated steel under tribological stimulation

Abstract: Hot corrosion of borate melt and interface chemistry of borate-coated steel Hot corrosion of borate melt and interface chemistry of borate-coated steel under tribological stimulation under tribological stimulation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…The authors highlighted the important role of physical chemistry of the borate melt for its tribological response. In another contribution, Tran et al [543] have analyzed the tribochemistry of borate melt/oxidized steel. They found that the oxidation reaction of borate melt on oxidized steel is due to interface reaction of the oxide particles.…”
Section: High Temperature Speciality Lubricantsmentioning
confidence: 99%
“…The authors highlighted the important role of physical chemistry of the borate melt for its tribological response. In another contribution, Tran et al [543] have analyzed the tribochemistry of borate melt/oxidized steel. They found that the oxidation reaction of borate melt on oxidized steel is due to interface reaction of the oxide particles.…”
Section: High Temperature Speciality Lubricantsmentioning
confidence: 99%
“…Sodium borate, Na2B4O7.10H2O, begins melting around 525 °C and can provide good lubricity on siding steel surfaces over 600-800 °C [22,23]. Results from ball-on-disc tribotesting showed different tribofilm structures on different mating surfaces.…”
Section: Sodium Boratementioning
confidence: 99%
“…The lower friction of borax glass could be the consequence of a high temperature of 900 °C, which is out of its optimal working condition and it was in a molten state. [22,23]. Results from ball-on-disc tribotesting showed different tribofilm structures on different mating surfaces.…”
Section: Sodium Boratementioning
confidence: 99%
“…Therefore, the reasonable number of dopants for a 4 × 4 G supercell could be 1 or 2 dopant atoms, which corresponds to the doping concentrations of 3.125 and 6.25%, respectively. It is worth mentioning that the compounds of all dopant elements have been widely used as lubricants/additives for high-temperature lubrication. ,, These atoms play the role of binders to keep the lubricant adhered onto the working surfaces. The simulations in this work show that the adhesion of G even at high temperatures improved significantly when these atoms were added.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Details about the size and the number of atoms of the simulation models are presented in Table . These systems were equilibrated for 10 ps using a time step of 1 fs and canonical (NVT) ensemble at four different temperatures from 900 to 1200 K, which are conventional temperatures for experimental hot tribotestes. , It is worth mentioning that the simulation time is equal or longer than that in other works , and sufficiently long to observe structural changes by the thermal onset. The FPMD simulations were performed using Γ-point sampling and a cutoff energy of 400 eV for the plane wave functions.…”
Section: Methodsmentioning
confidence: 99%